Sol–Gel Synthesis and Comprehensive Study of Structural, Electrical, and Magnetic Properties of BiBaO3 Perovskite - Faouzia Tayari; Kais Iben Nassar; João Pedro Carvalho; Sílvia Soreto Teixeira; Imen Hammami; Sílvia Rodrigues Gavinho; Manuel P. F. Graça; Manuel Almeida Valente (Gels)
In this study, BiBaO3 perovskite was successfully synthesized via the sol–gel method and thoroughly characterized to evaluate its structural, microstructural, dielectric, electrical, and magnetic properties. X-ray diffraction (XRD) confirmed the formation of a single-phase perovskite structure with high crystallinity. Scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX) revealed a uniform grain morphology and elemental composition consistent with the intended stoichiometry. Dielectric measurements exhibited strong frequency-dependent behavior, suggesting potential for capacitive applications. The electrical conductivity displayed thermally activated behavior, indicative of semiconducting characteristics. Magnetic measurements showed weak ferromagnetic behavior at room temperature, an unusual observation for undoped BaBiO3-based systems. This magnetism may stem from subtle structural distortions or compositional variations introduced during synthesis. Comparison with previously reported studies underscores the significant influence of the synthesis route and microstructural features on the multifunctional properties of BiBaO3. Overall, the results highlight the promise of sol–gel-derived BiBaO3 as a candidate for multifunctional electronic and magnetic applications.